The distinction between state and trait anxiety levels in patients with BPPV in comparison with healthy controls - Kalderon, Liran; Chaimoff, Moshe; Katz-Leurer, Michal (Frontiers in Psychology, 2022)
Introduction: An association exists between vestibular dysfunction and anxiety, yet a distinction between state and trait anxiety in patients with Benign Paroxysmal Positional Vertigo (BPPV) in comparison with healthy subjects hasn't been well established. The aim of this study is to assess both state and trait anxiety levels in patients with BPPV in comparison with healthy controls, and their relations with cardiac autonomic parameters. Materials and methods: A case-control study, that included patients with BPPV (N=18) referred to vestibular physiotherapy and gender and age matched healthy controls (N=18). All participants completed the State-Trait Anxiety Inventory (STAI) questionnaire, while heart-rate (HR) and heart-rate variability (HRV) measures were recorded. Results: Patients with BPPV (age range 32-66 years; 12 women and 6 men) showed a higher state anxiety level (10 points median difference, p=0.001) in comparison with healthy controls (age range 34-66 years; 12 women and 6 men), yet no differences were found in trait anxiety score or total STAI score. Only among patients with BPPV, a positive-moderate correlation was found between state anxiety and HR (r=0.53, p<0.05), and a negative moderate-strong correlation was found between state anxiety and HRV (r=-0.67, p<0.01). Discussion: Patients with BPPV don't differ from healthy subjects in terms of predisposition to feel anxious, and only their temporary state anxiety levels are higher in comparison with healthy controls. We recommend researchers and clinicians who assess anxiety levels in patients with BPPV to distinguish between anxiety as a temporary state (state anxiety) and anxiety as a personality trait (trait anxiety). Trial registration number (TRN) - ClinicalTrials.gov ID- NCT03867019